Allemaal beestjes. Mortaliteit en morbiditeit in Vlaanderen, 18de-20ste eeuw - Devos, Isabelle (Historische Economie en Ecologie, 2006)
This book treats the spectacular rise in life expectancy during the last three centuries. It is the first study to bring together both published and unpublished material about the history of the health of Belgian men and women and to analyze it critically. Isabelle Devos studies the mechanisms of the historic fall in the death rate in an original manner and answers the question why research on the causes of this decline has not progressed faster. While the discipline of historical demography orients the first part of her book, the discipline of historical epidemiology provides the perspective taken in the second part, in which the role of insects as spreaders of disease is explored. Essential in her study is the importance of local medical practitioners who already at the end of the Ancien Régime warned of the dangers present in the environment. Their 'ecological' thinking created a consciousness that was decisive for the further development of healthcare.